Imprinted MicroRNA Gene Clusters in the Evolution, Development, and Functions of Mammalian Placenta - Malnou, E. Cécile; Umlauf, David; Mouysset, Maïlys; Cavaillé, Jérôme (Frontiers in Genetics, 2019)
In mammals, the expression of a subset of microRNA (miRNA) genes is governed by genomic imprinting, an epigenetic mechanism that confers monoallelic expression in a parent-of-origin manner. Three evolutionarily distinct genomic intervals contain the vast majority of imprinted miRNA genes: the rodent-specific, paternally expressed C2MC located in intron 10 of the Sfmbt2 gene, the primate-specific, paternally expressed C19MC positioned at human Chr.19q13.4 and the eutherian-specific, maternally expressed miRNAs embedded within the imprinted Dlk1-Dio3 domains at human 14q32 (also named C14MC in humans). Interestingly, these imprinted miRNA genes form large clusters composed of many related gene copies that are co-expressed with a marked, or even exclusive, localization in the placenta. Here, we summarize our knowledge on the evolutionary, molecular and physiological relevance of these epigenetically-regulated, recently-evolved miRNAs, by focusing on their roles in placentation and possibly also in pregnancy diseases (e.g. preeclampsia, intrauterine growth restriction, preterm birth).